Management of Autoimmune Status Epilepticus - Kirmani, Batool F.; Barr, Donald; Robinson, Diana Mungall; Pranske, Zachary; Fonkem, Ekokobe; Benge, Jared; Huang, Jason H.; Ling, Geoffrey (Frontiers in Neurology, 2018)
Status Epilepticus is a neurological emergency with increased morbidity and mortality. Urgent diagnosis and treatment are crucial in order to prevent irreversible brain damage. In this mini review, we will discuss the recent advances in the diagnosis and treatment of autoimmune status epilepticus, a rare form of the disorder occasionally encountered the intensive care unit. Autoimmune status epilepticus can be refractory to anticonvulsant therapy. The presence of subacute onset of short-term memory loss with rapidly progressive encephalopathy, psychiatric symptoms with unexplained new onset seizures, imaging findings, CSF pleocytosis, and availability of antibody testing made the earlier diagnosis of autoimmune status epilepticus possible. Treatment of autoimmune status epilepticus includes high dose steroids, intravenous immunoglobulin therapy, or plasmapheresis. The goal is to maximize the effectiveness of anticonvulsant agents and find an optimal combination of therapies while undergoing immunomodulatory therapy in order to reduce morbidity and mortality.